Functional and molecular characterization of Bsister genes in the two model species: Arabidopsis thaliana and Eschscholzia californica - Tekleyohans, Dawit Girma; Justus Liebig University Giessen (My University, 2014)
Ovules are one of the most important organs for seed plants. Understanding their organogenesis has been at the center of research interest for long time that let to the identification of several genes that are involved in ovule development. This includes MADS box transcription factors such as Bsister genes. Bsister genes are identified more than a decade ago but so far only few species have been used to investigate their function. In this study the TRANSPARENT TESTA 16 (ABS) from Arabidopsis thaliana and ESCHSCHOLZIA CALIFORNICA BSISTER (EBS) from Eschscholzia californica were chosen to investigate the role of Bsister genes in eudicots. In addition to what was described in previous studies, additional phenotypes which are associated with ABS loss-of-function were found that includes defects in seed germination, seed and silique development. In comparison to wild type plants, the number of mature seeds in abs mutant is reduced to 33%. Furthermore, seed germination is also affected in abs mutant when grown on growth medium supplemented with different salt concentration. In order to investigate the genetic interaction between ABS and SHP genes, triple mutant lines were generated and characterized. The result shows that the triple mutant produces much more less number of seeds compared to abs mutant and these seeds appear to be shrunken in structure. In order to identify de-regulated genes in the triple mutants that resulted in defect in seed structure and plant fertility, expression analysis of selected genes that are known to be involved in either of programmed cell death, lipid metabolism, ovule or seed development was carried out. The expression analysis result shows that ABS, SHP1, and SHP2 directly or indirectly regulate these target genes expression in an independent and redundant manner.Characterization of EBS begins with its expression analysis using in situ hybridization and qRT-PCR techniques and the results shows that EBS expression starts prior to the ovule primordia formation but becomes restricted to the ovule at later developmental stages specifically strongly expressed in the inner integument and nucellus region of the ovule. Yeast two-hybrid technique was used to identify EBS protein interacting partners and the result showed that EBS interacts with B-class & C-class floral homeotic proteins. Furthermore, functional analysis of EBS via VIGS methods indicates that down-regulation of EBS transcripts causes abnormalities in developing seed structure while over-expression of EBS in Arabidopsis significantly alters the vegetative and floral organ morphogenesis that led to male sterility and also affects seed fatty acid composition. In order to use E. californica for future reverse genetics approach, an efficient stable genetic transformation protocol was optimized using developing seeds as explants. It was possible to produce somatic embryos that regenerate to fully-grown plants. The successful integration of the transgene was verified using molecular technique. This stable transformation protocol will be helpful for the functional characterization of genes which are difficult to analyze using transient gene knock-down methods.In general, this dissertation provides new findings that can strengthen the current understanding of Bsister gene function in angiosperm plant development. The study suggests that for a detailed understanding of Bsister genes, it is necessary to consider potential redundantly acting genes (that are mainly MADS-box genes) that have an overlapping expression pattern with Bsister genes. Besides that, the conservation and divergence pattern in molecular and functional aspects of Bsister genes in these two model species provides insights for further understanding of plant evolution and development.

Die weiblichen Reproduktionsorgane, die Ovulen, gehören zu den wichtigsten Organen der Samenpflanzen. Das Verständnis ihre Organogenese ist seit langem Thema intensiver Forschungen. Wichtige Gene, überwiegend Transkriptionsfaktoren, unter ihnen die Bsister Gene, konnten bereits als regulatorische Gene der Ovulenentwicklung identifiziert werden. Bislang wurden aber nur einige wenige Spezies auf ihre Bsister Genfunktionen hin untersucht. Als Ziel der Arbeit wurden die eudikotylen Bsister Gene TRANSPARENT TESTA16 (ABS) von Arabidopsis thaliana und ESCHSCHOLZIA CALIFORNICA BSISTER (EBS) von Eschscholzia californica für eine funktionelle Charakterisierung ausgewählt.ABS loss-of-function Mutationen beeinflussen die Samen- und Fruchtentwicklung, was bisher noch nicht gezeigt werden konnte. Im Vergleich mit dem Wildtyp ist die Zahl reifender Samen in abs Mutanten um 33% reduziert. Zusätzlich beträgt die Keimungsrate der Samen von abs Linien nur 25 % im Vergleich mit 96% für Wildtyp-Samen. Dieser Phänotyp-Komplex wird in der Dreifach-Mutante abs shp1 und shp2 noch deutlich verstärkt. Zusätzlich zeigt die Dreifach-Mutante eine veränderte Samenmorphologie, in der die Samen geschrumpft und zerknittert sind, im Vergleich zu der glatten und ovalen Struktur der Wildtyp-Samen. Die Suche nach von ABS, SHP1, und SHP2 reguliertenGenen erbrachte Entwicklungsgene aus unterschiedlichen Kategorien, wie z.B. dem programmierten Zelltod, dem Lipidmetabolismus oder der Samen- und Fruchtentwicklung. Die Untersuchung der Expression dieser potentiellen Zielgene offenbarte dabei eine funktionelle Redundanz von ABS, SHP1 und SHP2 bei deren Regulierung.Die Expressionsanalyse von EBS mit Hilfe der in situ Hybridisierung und der quantitativenreal-time PCR ergibt eine starke Aktivität in den Ovulenprimordien und beschränkt sich später auf die sich entwickelnden Ovulen. Des Weiteren findet sich eine starke Expression in den inneren Integumenten und im Nucellus der Ovulen. Mit Hilfe der yeast-two-hybrid Methode konnte gezeigt werden, das das EBS Protein mit floralen homöotischen Proteinen der B-Klasse und C-Klasse interagiert. Die Herunterregulation der EBS Funktion beeinflusste die Samenmorphologie und eine Überexprimierung von EBS im heterologen System Arabidopsis führte zu einer signifikanten Veränderung der vegetativen und floralen Organogenese, bis hin zur männlichen Sterilität der Pflanzen. Für E. californica als Modelorganismus für zukünftige reverse genetics Experimente wurde ebenfalls im Rahmen dieser Dissertation Protokolle für eine stabile genetische Transformation optimiert. Dabei wurden sich entwickelnde Samen als Explantate benutzt. Es konnten somatische Embryonen bis hin zu voll entwickelten Pflanzen regeneriert werden. Die erfolgreiche Integration der Transgene wurde mit molekularen Methoden bestätigt. Dieses Protokoll unterstützt die molekulare Analyse von Entwicklungsgenen, was mit transienten gene knock-down Methoden allein nur schwer erreicht werden kann.Generell unterstützen die Ergebnisse dieser Dissertation das Verständnis der Bsister Genfunktionen in der Ovulenentwicklung der Blütenpflanzen. Zusätzlich unterstreichen die Ergebnisse, dass es für eine vollständige Erfassung der Bsister Genfunktionen notwendig ist, potentielle redundant wirkende Gene (die vor allem MADS-Box-Gene), die einen überlappenden Expressionsmuster mit Bsister Gene zu prüfen. Die mit Hilfe der beiden Modellorganismen erarbeiteten molekularen und funktionalen Aspekte der Bsister Gene und deren Konservierung bzw. Diversifizierung werden einen wichtigen Einfluss auf zukünftige Untersuchungen haben, die sich mit der Evolution und der Entwicklung der Pflanzen beschäftigen.
Funktionelle und molekulare Charakterisierung von Bsister Gene in den beiden Modellpflaznen: Arabidopsis thaliana und Eschscholzia californica
Keywords: Arabidopsis thaliana; Eschscholzia californica; Bsister genes; ddc:570